Child Effects on Parental Negativity: The Role of Heritable and Prenatal Factors. Issue 5 (1st August 2020) - Liu, Chang; Ji, Linying; Chow, Sy‐Miin; Kang, Boyoung; Leve, Leslie D.; Shaw, Daniel S.; Ganiban, Jody M.; Natsuaki, Misaki N.; Reiss, David; Neiderhiser, Jenae M.
Abstract : This study examined two possible mechanisms, evocative gene–environment correlation and prenatal factors, in accounting for child effects on parental negativity. Participants included 561 children adopted at birth, and their adoptive parents and birth parents within a prospective longitudinal adoption study. Findings indicated child effects on parental negativity, such that toddlers' negative reactivity at 18 months was positively associated with adoptive parents' over‐reactive and hostile parenting at 27 months. Furthermore, we found that child effects on parental negativity were partially due to heritable (e.g., birth mother [BM] internalizing problems and substance use) and prenatal factors (e.g., BM illicit drug use during pregnancy) that influence children's negative reactivity at 18 months. This study provides critical evidence for "child on parent" effects.